1964
DOI: 10.1530/acta.0.0450079
|View full text |Cite
|
Sign up to set email alerts
|

Further Notes on the Interaction of Spironolactone and Deoxycorticosterone Acetate in Dogs

Abstract: Administration of DCA induced typical mineralocorticoid effects in a dog, namely the retention of urinary Na and Cl and the loss of K ions. Coadministration of spironolactone orally at several doses neutralized the effect on K, but produced a rate-limited inhibition of Na and Cl retention, by altering tubular reabsorption of the ions. Plasma levels of spironolactone did not appear to be a factor limiting the Na and Cl response. Interpretation of these data indicates that spironolactone inhibited only one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These authors found that in man the acute kaliuretic action of aldosterone was not sufficiently constant as to allow a clear assessment of the blocking action of spironolactone upon the renal handling of potassium. More recently Kagawa, Bouska, and Anderson (1964) found that the administration of spironolactoneinhibited the effect of 1 1-de-oxycorticosterone on the renal handling of potassium. This blockade was complete.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that in man the acute kaliuretic action of aldosterone was not sufficiently constant as to allow a clear assessment of the blocking action of spironolactone upon the renal handling of potassium. More recently Kagawa, Bouska, and Anderson (1964) found that the administration of spironolactoneinhibited the effect of 1 1-de-oxycorticosterone on the renal handling of potassium. This blockade was complete.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the similarity in chemical structure, it might be suggested that both drugs are active in this regard. Further, it is of interest to note that aldadiene retains the antimineralcorticoid effects of spironolactone ( 12 ) . …”
Section: Materials and Methods Nonfasted Malementioning
confidence: 99%